Perancangan Simulasi Sistem Kontrol Volume Pada Dua Tangki Air Melalui Telegram - Sabril Prajudith Pangestu; Made Bagus Astika Yasa; I Wayan Dimas Ariawan; Kadek Amerta Yasa; I Made Purbawa; I Ketut Parti; Anak Agung Ngurah Made Narottama; Anak Agung Ngurah Gde Sapteka (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
In this modern era, the community (especially in urban areas) can get enough water supply from PDAM (Regional Water Supply Company). In other cases, not all houses in the village or needs like farms or fields can get enough water supply. For example, technology for distributing and monitoring water from tanks to farms or agriculture is also still conventional and limited by visiting and opening water taps at the location. For this reason, we need a control system that can monitor and control the volume of water in several tanks through one application display on smartphones such as Telegram. Using NodeMCU ESP8266 as the microcontroller base, the ultrasonic sensor as a water volume measuring sensor, and the mini water pump, the condition of the water volume and all the changes can always be monitored through notifications on Telegram. In addition, the system can also be controlled automatically or manually through the commands provided on the telegram. We use Telegram as a control system, and monitoring the volume of water tanks in more than one tank can be the right alternative in designing a water tank control system. One Telegram bot can monitor and control more than one tank, where every tank has an individual ESP8266 module and ultrasonic sensor installed.